If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8x-37=-5+8(-7x+2)
We move all terms to the left:
-8x-37-(-5+8(-7x+2))=0
We calculate terms in parentheses: -(-5+8(-7x+2)), so:We get rid of parentheses
-5+8(-7x+2)
determiningTheFunctionDomain 8(-7x+2)-5
We multiply parentheses
-56x+16-5
We add all the numbers together, and all the variables
-56x+11
Back to the equation:
-(-56x+11)
-8x+56x-11-37=0
We add all the numbers together, and all the variables
48x-48=0
We move all terms containing x to the left, all other terms to the right
48x=48
x=48/48
x=1
| -612=1.7p+1.9p | | 2x+3x-4=7x-2 | | 2(3g+2)=1/2(12g+g) | | 1/2m+2=3/4m-12 | | 32x-1.7x+5.5=10 | | -7(x+4)+7=-3x+3 | | -6.12=1.7p+1.9p | | 21-8x=6x | | 14x+5=9+21x | | 3(1-m)=-4m-1 | | 1.50r+15=2.25r | | 15=7r-6 | | 7(3x-5)=21+7x | | (g+4)-3g=1-6 | | 6.1x/9.3=8.7x-4.5/7.22 | | -4(6+k)=-80 | | 3x+2=2+1x | | 3.25x-0.4=3 | | (6.1x)/9.3=((8.7x)-4.5)/7.22 | | 8-(6+2x)=100 | | 15x+3(3x1)=16x+3 | | 9+3/4x=7/8-x10 | | 155=2+9x | | 3x^2+27x-7.7=0 | | 2.22y+5.27=4.81-1.99y | | 12•5÷15-13=y | | 34x+99=3(14x+9) | | 3k+5k-6=8k+3-9 | | 3.2x+0.5(7.3-x)=4.7-6.4(×-2.1) | | 9a+8=44 | | 7.5/n=33.75 | | 2/5(25b)-40=1/4(16b+8 |